Phenology, biomass and associated species of alligator weed at Biratnagar, Nepal - Niroula, Bhabindra (Nepalese Journal of Biosciences, 2013)
DOI: http://dx.doi.org/10.3126/njbs.v2i0.7502 Nepalese Journal of Biosciences 2 : 148-150 (2012)